Production Line Efficiency - Shaaban, Sabry (Business Expert Press, 2013)
Ebook from IG Library ; This book covers the area of unpaced and unbalanced production lines. You will find an up-to-date discussion of how designing these lines can be made more efficient by taking advantage of inherent imbalance—for example, operators who work at different speeds—a concept that has traditionally been seen as an obstacle to efficient production. A series of experiments are presented to illustrate the issues involved in improving performance through production line imbalance.